PENERAPAN MODEL COLLABORATIVE LEARNING UNTUK MENINGKATKAN LITERASI MATEMATIS DAN AKTIVITAS BELAJAR SISWA DI KELAS VII SMP - Febriliati, Febriliati; Marlina, Mira; Ayuningtyas, Vidya (LPPM Universitas Bina Bangsa, 2024)
This study aims to determine the application of the Collaborative Learning model to improve mathematical literacy and student learning activities in class VII of junior high school. The method used in this study is quantitative using experimental research. The population in this study were all students of class VII of SMPN 1 Puloampel, the sample was taken using purposive sampling technique so that the samples obtained were students of class VII-B as the control class and class VII-A as the experimental class with a total of 25 students in each class. Data collection techniques used 5 essay tests, students' mathematical literacy skills, and learning activity questionnaires. The results of data analysis showed that the application of the Collaborative Learning model to improve mathematical literacy and student learning activities was better than conventional learning